Sex/Gender-Specific Medicine in the Gastrointestinal Diseases - Kim, Nayoung; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
Sex/gender - specific medicine (SGM) is defined as the practice of medicine based on the understanding that biology and social roles are important in men and women for disease prevention, screening, diagnosis, and treatment. Current research demonstrates differences in disease incidence, symptomatology, morbidity, and mortality based on sex and gender. Sex/gender-specific medicine is a fundamental aspect of tailored therapy and precision medicine. Therefore, the variables must be considered in medical education and practice as well as in research models ranging from human participants, animals and cells. Gastroenterology is very big and important division of Internal Medicine, which include esophagus, stomach, small and large intestine, pancreatobiliary tract and liver. Nowadays estrogen is known to play a key role in the prevention of colon cancer and progression of liver cirrhosis and hepatocellular carcinoma, especially in women. This book covers the sex/gender-specific medicine in the area of gastrointestinal (GI) tract in the adults as well as in the pediatrics and in the gut microbiota.
1.Sex/gender-specific medicine -- 2.The difference of sex and gender in the gastrointestinal diseases -- 3.The metabolism of estrogen and testosteron -- 4.Esophagus -- 5.Stomach -- 6.Pancreas and biliary diseases -- 7.Liver -- 8. Colon -- 9. Brain-Gut-Microbiome axis -- 10. Sex difference of gut microbiota -- 11. Overlap syndrome of FGIDs (functional gastrointestinal disorders) -- 12. Sex difference of gastrointestinal diseases in the pediatrics -- 13. Pharmacodynamics and Pharmacokinetics of gastrointestinal drugs -- 14. Sex/gender-specific medicine education and work-l ife conflict and its health effects on Korean gastroenterologists according to age and sex.
Keywords: Gastroenterology; Internal medicine; Gastroenterology; Internal Medicine; Gastrointestinal Diseases; Sex Factors